The impact, mechanisms and prevention strategies of environmental endocrine disruptors on male reproductive health - Han, Xiaoyan; Jin, Xiaolong (Frontiers in Endocrinology, 2025)
BackgroundEnvironmental endocrine disruptors (EEDs) including heavy metals, plasticizers, and persistent organic pollutants have been increasingly linked to declining male reproductive health globally. While epidemiological associations are well-established, the underlying molecular mechanisms and long-term consequences require systematic evaluation.ObjectivesThis review synthesizes current evidence on EED impacts on male reproductive health, focusing on molecular mechanisms, population-based evidence, transgenerational effects, and intervention strategies.MethodsWe conducted comprehensive literature searches across PubMed, Web of Science, and Scopus (2019–2024) to identify peer-reviewed studies on EED reproductive toxicity, including mechanistic investigations, epidemiological studies, and intervention research.ResultsEEDs disrupt male reproduction through multiple pathways: androgen and estrogen receptor interference, oxidative stress induction, mitochondrial dysfunction, and epigenetic modifications. Population studies demonstrate consistent associations between EED exposure and reduced sperm quality, with effect sizes varying by exposure level and chemical type. Animal studies provide compelling evidence for transgenerational inheritance of reproductive dysfunction through epigenetic mechanisms, though human evidence remains limited. Workplace protection measures, environmental remediation, and policy interventions show promise but require broader implementation.ConclusionsEEDs pose significant threats to male reproductive health through complex, interconnected mechanisms. While substantial progress has been made in understanding these effects, critical gaps remain in mixture toxicology, low-dose effects, and transgenerational impacts in humans. Enhanced biomonitoring, mechanism-based interventions, and strengthened regulatory frameworks are essential for protecting current and future reproductive health.